The use of OCT in good visual acuity MOGAD and AQP4-NMOSD patients; with and without optic neuritis. Issue 4 (October 2021) - Roca-Fernández, A; Camera, V; Loncarevic-Whitaker, G; Messina, S; Mariano, R; Vincent, A; Sharma, S; Leite, MI; Palace, J
Myelin oligodendrocyte-antibody-associated disease (MOGAD) often presents with severe optic neuritis (ON) but tends to recover better than in aquaporin-4 antibody neuromyelitis optica spectrum disorder (AQP4-NMOSD). We measured OCT and VEP in MOGAD and AQP4-NMOSD eyes with good visual function, with or without previous ON episodes. Surprisingly, OCT and/or VEPs were abnormal in 84% MOGAD-ON versus 38% AQP4-NMOSD-ON eyes (p = 0.009) with good vision, compared with 18% and 17% respectively of eyes with no previous ON. A sub-group with macular OCT performed as part of a research study confirmed both retinal and macular defects in visually-recovered MOGAD eyes. These findings have implications for investigation and management of MOGAD patients.